PENINGKATAN MOTIVASI BELAJAR MATEMATIKA SISWA DALAM PEMBELAJARAN DARING MELALUI PERAN ORANG TUA DAN KOMPETENSI GURU - Rismaini, Lili (STKIP Pesisir Selatan, 2022)
This study aims to determine how high the influence of the role of parents and teacher competence on students' learning motivation in online learning at SMP N 1 Ranah Pesisir. This type of research is quantitative with an explanatory research approach. There were 105 students of SMP N 1 Ranah Pesisir who were selected as samples according to the cluster random sampling technique. Data were collected using a questionnaire with a 5-point Likert measurement scale. The results of the study using multiple linear regression analysis showed that the results of the minor analysis were partially accepted. H1 was accepted proving that there was a significant positive effect of the parent's role on students' learning motivation, and H2 was accepted, meaning that there was a significant positive effect of teacher competence on student learning motivation, while the results of the major analysis were H3 is accepted, which means that there is a significant positive effect of the role of parents and teacher competence on student learning motivation. The contribution of the variables of the role of parents and teacher competence to students' learning motivation in online learning reached 65.3 percent, the remaining 34.7 percent were other factors outside of the research